The Role Of Social Workers In Low Vision Rehabilitation Services At The Worth Foundation - Yudistira, Thomas; Hastin Trustisari (Pubmedia Social Sciences and Humanities, 2024)
Low vision is a form of visual impairment that limits daily activities and cannot be corrected with glasses, contact lenses, medication, or surgery (Jennifer Hissett 2008, 1032-33). Social workers have unique abilities in carrying out their role as professional experts in implementing low vision services at LAYAK Foundation's. One of the social institutions in Jakarta that participates in the implementation of social welfare that raises the issue of low vision is Yayasan Pelayanan Anak dan Keluarga (LAYAK). So the researcher wants to see what role social workers can play in helping low vision disabilities overcome limitations through the LAYAK Foundation's rehabilitation services. Research using qualitative methods using observation techniques, interviews and also using documentation studies, researchers focus the problem on the role of social workers carried out in rehabilitation services at LAYAK Foundation. Based on Walter A Fridlander's theory, the role of social workers is divided into 7 roles, namely as a catalyst, informator, mediator, motivator, counselor, facilitator and educator. In the research findings, it can be concluded that the role of social workers in increasing client independence in rehabilitation services at the LAYAK Foundation has advantages and disadvantages.